The Role of Cardiac Side Population Cells in Cardiac Regeneration - Yellamilli, Amritha; van Berlo, Jop H. (Frontiers in Cell and Developmental Biology, 2016)
The heart has a limited ability to regenerate. It is important to identify therapeutic strategies that enhance cardiac regeneration in order to replace cardiomyocytes lost during the progression of heart failure. Cardiac progenitor cells are interesting targets for new regenerative therapies because they are self-renewing, multipotent cells located in the heart. Cardiac side population cells (cSPCs), the first cardiac progenitor cells identified in the adult heart, have the ability to differentiate into cardiomyocytes, endothelial cells, smooth muscle cells, and fibroblasts. They become activated in response to cardiac injury and transplantation of cSPCs into the injured heart improves cardiac function. In this review, we will discuss the current literature on the progenitor cell properties and therapeutic potential of cSPCs. This body of work demonstrates the great promise cSPCs hold as targets for new regenerative strategies.